Noether's symmetry theorem for nabla problems of the calculus of variations - Martins, N.
We prove a Noether-type symmetry theorem and a DuBoisReymond necessary optimality condition for nabla problems of the calculus of variations on time scales. © 2010 Elsevier Ltd. All rights reserved.